2005
DOI: 10.1103/physrevlett.95.204501
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Collective Dynamics in Suspensions of Confined Swimming Particles

Abstract: Direct simulations of large populations of confined hydrodynamically interacting swimming particles at low Reynolds number are performed. Hydrodynamic coupling between the swimmers leads to large-scale coherent vortex motions in the flow and regimes of anomalous diffusion that are consistent with experimental observations. At low concentrations, swimmers propelled from behind (like spermatazoa) strongly migrate toward solid surfaces in agreement with simple theoretical considerations; at higher concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
407
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(439 citation statements)
references
References 24 publications
28
407
3
1
Order By: Relevance
“…Such a model is in a coarse grained level and without hydrodynamic interactions [69,70]. The model is composed of self-propelled particles moving with constant speed v 0 in two dimensions.…”
Section: Microscopic Modelmentioning
confidence: 99%
“…Such a model is in a coarse grained level and without hydrodynamic interactions [69,70]. The model is composed of self-propelled particles moving with constant speed v 0 in two dimensions.…”
Section: Microscopic Modelmentioning
confidence: 99%
“…Examples of such cooperative dynamical effects include sperms beating in harmony [2], metachronal waves in cilia [3][4][5], formation of bound states between rotating microorganisms [6], and flocking behavior of red blood cells moving in a capillary [7]. For a collection of free swimmers, such as microorganisms [8], hydrodynamic interactions have been shown to lead to instabilities [9,10] that can result in complex dynamical behaviors [10,11]. In the context of simple microswimmer models where hydrodynamic interactions coupled to internal degrees of freedom can be studied with minimal complexity, it has been shown that the coupling could result in complex dynamical behaviors such as oscillatory bound states between two swimmers [12], and collective many-body swimming phases [13,14].…”
mentioning
confidence: 99%
“…10,11 For instance, flagellates propelled from behind by a rotating helical bundle are "pushers" while those swimming towards the bundle are "pullers." These are the examples of dipole swimmers, so-called because the disturbance flow generated by the swimmer has the form of that due to a force dipole.…”
Section: Pushers and Pullers-the Implicit Swimming Gaitmentioning
confidence: 99%
“…Analytical simplifications to the latter process are possible for very slender or nearly spherical bodies. [9][10][11] It is these simplifications that we leverage to achieve a general technique for modeling swimming animalcules.…”
Section: Introductionmentioning
confidence: 99%